2008
DOI: 10.1364/ol.33.002182
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared luminescence of RbPb_2Cl_5:Bi crystals

Abstract: A wideband near-IR (NIR) luminescence centered at 1080 nm was found in a RbPb(2)Cl(5):Bi single crystal grown by the Bridgman technique. Absorption, luminescence, and excitation of luminescence spectra were investigated at room and cryogenic temperatures. The luminescence was proposed to be due to the (3)P(1)-->(3)P(0) transition in Bi(+) ion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
52
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 10 publications
1
52
1
Order By: Relevance
“…It was shown that several of such subvalent bismuth forms (Bi + [4][5][6][7][8][9][10][11], Bi 5 3+ [12][13][14][15][16], Bi 2 8+ [16]) demonstrate the broadband NIR PL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that several of such subvalent bismuth forms (Bi + [4][5][6][7][8][9][10][11], Bi 5 3+ [12][13][14][15][16], Bi 2 8+ [16]) demonstrate the broadband NIR PL.…”
Section: Introductionmentioning
confidence: 99%
“…Univalent bismuth impurity, observed in several chloride [6][7][8][9][10], iodide [18,19] and nonhalide crystal phases [11,[20][21][22][23][24][25], represents the simplest form of NIR photoluminescent subvalent bismuth center. It possesses the 6p 2 open shell electronic configuration with the 3 P 0 ground state and 3 P 1 , 3 P 2 low lying excited states.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain a rational explanation of the observed photophysical 5 behaviors, next we performed a detailed quantum chemistry calculation on Bi 8 2+ polycation using the Amsterdam Density Functional (ADF) program package developed by Baerends et al. 20,21 The geometry of Bi 8 2+ obtained from the XRD analysis was used for the following calculations.…”
mentioning
confidence: 99%
“…Since the discovery of the broadband near-infrared (NIR) photoluminescence from bismuth doped glasses [1][2][3][4][5] and crystalline materials [6][7][8][9][10][11][12][13][14][15][16][17][18][19] the nature of corresponding luminescent species is widely discussed. The Bi 3+ ion in the common oxidation state +3 has no optical transitions in NIR and the observed emission was attributed to possible Bi 5+ , 1 Bi 2+ , 20 Bi + , 21 Bi 0 , 8,9,22 Bi 2 À , Bi 2 2À , 23 and bismuth cluster species.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33] It is interesting that NIR luminescence has also been detected from the bismuth dimer anion (Bi 2 2À ) in the (K-crypt) 2 Bi 2 crystal phase. 34 It was also demonstrated that the univalent bismuth cation (Bi + ) is the NIR emitter in the ternary halide crystals KAlCl 4 , KMgCl 3 , RbPb 2 Cl 5 , and CsCdCl 3 , 14,17,18,35,36 where Bi + substitutes isomorphically for the large alkali cations. On the other hand, it seems that several different emitters contribute to the net NIR photoluminescence in Bi-doped SiO 2 and GeO 2 -based glasses.…”
Section: Introductionmentioning
confidence: 99%